2021
DOI: 10.1142/s179354582150019x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in mandibular bone microchemical quality after radiation therapy and underlying systemic malignancy: A pilot study

Abstract: Radiation therapy (RT) is a treatment option for head and neck cancer (HNC), but 2% of RT patients may experience damage to the jawbone, resulting in osteoradionecrosis (ORN). The ORN can manifest years after RT exposure. Changes in the local microchemical bone quality prior to the clinical manifestation of ORN could play a key role in ORN pathogenesis. Chemical bone quality can be analyzed using Fourier transform infrared spectroscopy (FTIR), that is applied to examine the effects of cancer, chemotherapy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…13 Previous biochemical analytic studies indicated that irradiated bone is characterized by altered material properties and abnormalities in the chemical composition and structure of the bone matrix. [14][15][16] In irradiated hindlimb mouse models, bone mineral and matrix compositions were studied using Raman spectroscopy. These animal studies demonstrated changes in the bone quality and its mechanical competence contributing toward fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous biochemical analytic studies indicated that irradiated bone is characterized by altered material properties and abnormalities in the chemical composition and structure of the bone matrix. [14][15][16] In irradiated hindlimb mouse models, bone mineral and matrix compositions were studied using Raman spectroscopy. These animal studies demonstrated changes in the bone quality and its mechanical competence contributing toward fragility fractures.…”
Section: Introductionmentioning
confidence: 99%